Climate Change and Reservoir Impacts on 21st-Century Streamflow and Fluvial Sediment Loads in the Irrawaddy River, Myanmar - Sirisena, T. A. J. G.; Maskey, Shreedhar; Bamunawala, Janaka; Ranasinghe, Roshanka (Frontiers in Earth Science, 2021)
Reservoirs play a vital role in water resource management, while also contributing to alterations in downstream flow regimes and sediment load in the river. On the other hand, variations on streamflow and fluvial sediment loads can also result from climate change effects. Here, we assess future changes in streamflow and sediment load due to both climate change and planned reservoirs in the Irrawaddy River Basin, Myanmar. The Soil Water Assessment Tool (SWAT) is used to project streamflow and sediment loads during 2046-2065 (mid-century), and 2081-2100 (end-century) periods under the two end-member Representative Concentration Pathways (i.e., RCP 2.6 and RCP 8.5) with and without planned reservoirs. Results show that compared to the baseline period (1991-2005), streamflow and sediment loads are projected to substantially increase during mid- and end- century periods when planned reservoirs are not considered (i.e., with climate change forcing only). Under RCP 2.6 and RCP 8.5, streamflow at the basin outlet is projected to increase by 8% - 17% and 9% - 45%, while sediment loads are projected to increase by 13% - 26% and 18%-75%, respectively by the end-century period. When reservoirs are included, while annual streamflow at the basin outlet does not show a significant difference compared to the climate change only case (for any RCP and for both future time periods considered), annual sediment loads at the basin outlet are projected to slightly decrease (compared to the climate change only case) by 4% - 6% under RCP 8.5 during the end-century period. At seasonal time scales however, streamflow and sediment loads at the basin outlet are significantly affected by upstream reservoirs. During the monsoon periods, the presence of planned reservoirs is projected to decrease streamflow at the basin outlet by 6% - 7 %, while during non-monsoon periods, the reservoirs result in an increase of 32% - 38% in the streamflow at the outlet under RCP 8.5 during the end-century period. Similarly, for the same period and RCP 8.5, due to the planned reservoirs, sediment load is projected to decrease by 9% - 11% and increase by 32% - 44% in monsoonal and non-monsoonal periods, respectively.